Engineering mechanics dynamics - Riley, William Franklin (John Wiley & Sons, 1993)
Offering a fresh approach to the study of mechanical engineering, this is part of a two-volume work which contains flexible coverage of kinematics and kinetics. This volume concentrates on dynamics.